Eelctronic transitions in slow collisions of atoms and molecules. V- Multichannel Eikonal approximation for the differential (p+, H) excitation and rearrangement collisions - Chen, Joseph; Takeshi, Ishihara; Ponce, Victor Hugo; Watson, Kenneth (American Physical Society, 1973)
Fil: Chen, Joseph University of Californi; Estados Unidos